2017
DOI: 10.1111/pim.12448
|View full text |Cite
|
Sign up to set email alerts
|

Resiniferatoxin modulates the Th1 immune response and protects the host during intestinal nematode infection

Abstract: In the early stage of the intestinal phase of Trichinella spiralis infection, the host triggers a Th1-type immune response with the aim of eliminating the parasite. However, this response damages the host which favours the survival of the parasite. In the search for novel pharmacological strategies that inhibit the Th1 immune response and assist the host against T. spiralis infection, a recent study showed that resiniferatoxin had anti-inflammatory activity contributed to the host in T. spiralis infection. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 68 publications
0
33
0
4
Order By: Relevance
“…It is natural that increasing the infection dose increases ML burden due to increase of NBL. The lower RCI in the low-infective-dose group may be due to the presence of significant Th2 and Treg immune responses, which suppress the Th1 immune response and promote worm expulsion [12,20]. Meanwhile, a significant Th17 immune response in the low-infective-dose group participated in worm expulsion at the intestinal stage [26].…”
Section: Figure 2 Dynamics Of Cd4+ T Cells and Cd8+ T Cells During Tmentioning
confidence: 99%
See 2 more Smart Citations
“…It is natural that increasing the infection dose increases ML burden due to increase of NBL. The lower RCI in the low-infective-dose group may be due to the presence of significant Th2 and Treg immune responses, which suppress the Th1 immune response and promote worm expulsion [12,20]. Meanwhile, a significant Th17 immune response in the low-infective-dose group participated in worm expulsion at the intestinal stage [26].…”
Section: Figure 2 Dynamics Of Cd4+ T Cells and Cd8+ T Cells During Tmentioning
confidence: 99%
“…The aim of the Th1-type immune response is to eliminate the parasite. However, this response damages the host, which favors the survival of the parasite [20]. The Th1 type cytokine IL-12 delays worm expulsion and increases worm burden in an IFNγ-independent manner [50].…”
Section: As the Lowest Infection Dose In Pigsmentioning
confidence: 99%
See 1 more Smart Citation
“…PAMPs derived from helminth parasites induce the activation and maturation of dendritic cells [147,148], promoting the development of the Th1 immune response [149], which results in a significant increase of Th1 cytokines such as IL-12 [150][151][152], INF-γ [149][150][151][152][153], IL-1β [152,154], and TNF-α [150][151][152]155] (Figure 5). However, in recent years, several studies have shown that this immune response of Th1 type favors infection by helminth parasites.…”
Section: Immune System Activation By Parasitic Helminth Infectionmentioning
confidence: 99%
“…Although TNF-α, a potent pro-inflammatory cytokine [9,10] was the first cytokine discovered that is secreted by adipose tissue [11], the leptin was the first molecule with hormonal activity that is secreted by adipocytes. Since then, multiple molecules called adipokines have been discovered as factors that are secreted by adipocytes or by the stromal-vascular fraction, composed mainly by macrophages, neutrophils, lymphocytes, fibroblast, and endothelial cells.…”
Section: Molecules Secreted By Adipocytes and Stromal-vascular Fractionmentioning
confidence: 99%